Thermally expandable microsphere and application of the same
The thermal expansion microsphere, with a defined particle diameter ratio and specific components, addresses heat resistance and shrinkage issues, enabling stable, lightweight molded bodies with improved appearance.
Patent Information
- Application Number
- JP2023118778
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-31
AI Technical Summary
Existing thermal expansion microspheres face issues with inadequate heat resistance, shrinkage during high temperatures or prolonged heating, leading to unsatisfactory lightweight molded bodies with poor appearance and stability.
A thermal expansion microsphere containing a thermoplastic resin and a foaming agent, with specific conditions such as a particle diameter ratio (D1/D0) of 1.2 or more, and inclusion of components like carboxyl group-containing monomers and thermal curing agents, to maintain shape and stability during expansion.
The solution enables the production of lightweight molded bodies with excellent appearance and stability, even at high temperatures or extended heating times, by minimizing contraction and maintaining the introduced shape.
Smart Images

Figure 2025015897000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to heat-expandable microspheres and applications thereof. [Background technology]
[0002] Thermally expandable microspheres (thermally expandable microcapsules), which are fine particles with a thermoplastic resin outer shell and a foaming agent encapsulated inside, have the characteristic of expanding when heated. Heat-expandable microspheres are generally used by blending them with other base materials and expanding the blend by heating the mixture. This method allows the base materials to have design properties or cushioning properties and to be made lighter. Heat-expandable microspheres that use a blowing agent having a boiling point equal to or lower than the softening point of the thermoplastic resin constituting the shell are widely known. For example, Patent Document 1 discloses a thermoplastic resin that uses a vinylidene chloride copolymer, an acrylonitrile copolymer, or an acrylic ester copolymer, and a blowing agent that mainly contains a hydrocarbon such as isobutane or isopentane.
[0003] In addition, when the composition is used together with a base component to form a molded product, the surface of the heat-expandable microspheres is excellent and the mechanical properties of the base component are not impaired, and the heat-expandable microspheres can be molded into lightweight molded products. The expansion start temperature and maximum expansion temperature of the heat-expandable microspheres are T s (℃) and T max (℃), and T max (℃) displacement in L max (μm), 120 <T s ≦250, 0≦T max -T s <30 and 0 <L max Patent Document 2 discloses one that satisfies the requirement of ≦600. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 42-26524 [Patent Document 2] JP 2011-256224 A Summary of the Invention [Problem to be solved by the invention]
[0005] It was confirmed that the heat-expandable microspheres disclosed in Patent Document 1 can be efficiently expanded when heated to a relatively low temperature, but when heated to a higher temperature or for a long period of time, the heat resistance of the microspheres is insufficient and they undergo a phenomenon known as "sag," in which the microspheres significantly shrink when heated. This not only prevents the molded article from being sufficiently lightweight, but also impairs the appearance due to the generation of dents, etc. In addition, it was confirmed that the heat-expandable microspheres disclosed in Patent Document 2 can give molded articles with excellent surface smoothness, but have insufficient expansion performance and tend to shrink after expansion, so that their performance as a weight-reducing agent is unsatisfactory, and furthermore, lightweight molded articles cannot be stably obtained in some cases.
[0006] Thus, there have been no heat-expandable microspheres that can stably produce lightweight molded articles with excellent appearance even when the molded articles are produced at high temperatures or for long heating periods. An object of the present invention is to provide heat-expandable microspheres which enable stable production of lightweight molded articles with excellent appearance, and uses thereof. [Means for solving the problem]
[0007] As a result of extensive investigations, the present inventors have found that specific heat-expandable microspheres can solve the above problems, and have arrived at the present invention. That is, the present invention relates to heat-expandable microspheres which contain an outer shell containing a thermoplastic resin (A) and a blowing agent (B) encapsulated in the outer shell and vaporized by heating, and which satisfy the following condition 1: Condition 1: In thermogravimetry, the ratio (D1 / D0) of the average particle size D1 of the heat-treated heat-expandable microspheres when the blowing agent content is reduced by 95% by weight to the average particle size D0 of the heat-expandable microspheres before the heat treatment is 1.2 or more.
[0008] The heat-expandable microspheres of the present invention preferably further satisfy at least one of the following requirements 1) to 3). 1) The thermoplastic resin (A) is a polymer of a polymerizable component containing a carboxyl group-containing monomer. 2) Contains a component (C) having thermosetting properties. 3) The following condition 2 is met. Condition 2: In thermogravimetry, the heat-expandable microspheres have a circularity of 0.8 or more after heat treatment when the blowing agent content is reduced by 95% by weight.
[0009] The hollow particles of the present invention are expanded products of the above-mentioned heat-expandable microspheres. The microparticle-coated hollow particles of the present invention contain the above-mentioned hollow particles and microparticles that are coated on the outer surface of the outer shell of the hollow particles.
[0010] The composition of the present invention contains at least one member selected from the group consisting of the heat-expandable microspheres, the hollow particles, and the fine particle-coated hollow particles, and a base component. The molded article of the present invention is obtained by molding the above composition. Effect of the Invention
[0011] The heat-expandable microspheres of the present invention can be used to stably produce lightweight molded articles with excellent appearance. The hollow particles of the present invention are expanded products of the above-mentioned heat-expandable microspheres, and therefore are lightweight with reduced shrinkage. The fine particle-coated hollow particles of the present invention contain the above-mentioned hollow particles, and therefore are lightweight with reduced shrinkage. Since the composition of the present invention contains at least one of the above heat-expandable microspheres, hollow particles, and microparticle-coated hollow particles, it is possible to stably produce molded articles which are lightweight and have excellent appearance. The molded article of the present invention is obtained by molding the above composition, and is therefore lightweight and has excellent appearance. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic diagram showing an example of heat-expandable microspheres. [Diagram 2] FIG. 2 is a schematic diagram showing an example of fine particle-coated hollow particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] [Thermally expandable microspheres] The heat-expandable microspheres of the present invention contain an outer shell containing a thermoplastic resin (A) and a blowing agent (B) that vaporizes when heated, and the microspheres as a whole exhibit heat expandability (the property that the entire microsphere expands when heated). The heat-expandable microspheres of the present invention may have a core-shell structure having a shell 6 containing a thermoplastic resin and a core 7 essentially containing a foaming agent, as shown in FIG.
[0014] The heat-expandable microspheres of the present invention satisfy the following condition 1. Condition 1: In thermogravimetry, the ratio (D1 / D0) of the average particle size D1 of the heat-treated heat-expandable microspheres when the blowing agent content is reduced by 95% by weight to the average particle size D0 of the heat-expandable microspheres before the heat treatment is 1.2 or more.
[0015] Generally, when the heat history is lower than that experienced by the heat-expandable microspheres until their maximum expansion, most of the foaming agent contained therein is retained in the heat-expandable microspheres or their expanded product, which is the heat-treated product, and no significant weight loss occurs. On the other hand, when the heat history is greater than that experienced at the maximum expansion, the shell of the expanded product of the heat-expandable microspheres (heat-treated product of the heat-expandable microspheres) becomes very thin, and the vaporized foaming agent escapes from the shell of the expanded product, causing the expanded product to shrink without maintaining its size, and to become smaller than the size before the heat treatment. The heat-expandable microspheres of the present invention satisfy the above-mentioned condition 1. Even when the heat history is much greater than that at the maximum expansion (when the blowing agent content is reduced by 95% by weight in thermogravimetry), the D1 / D0 ratio is 1.2 or more, so that the contraction of the expanded body is suppressed and the shape of the pores introduced by the expansion of the heat-expandable microspheres is maintained, thereby enabling the stable production of lightweight molded articles with excellent appearance and suppressed surface depressions.
[0016] The D1 / D0 of the heat-expandable microspheres of the present invention is preferably at least 1.3, more preferably at least 1.4. There is no particular upper limit to D1 / D0, but it is preferably 3, more preferably 2.5. In the thermogravimetry, the average particle size D1 of the heat-treated heat-expandable microspheres when the blowing agent content is reduced by 95% by weight, and the average particle size D0 of the heat-expandable microspheres before the heat treatment are measured by the method described in the Examples.
[0017] The average particle size D0 of the heat-expandable microspheres of the present invention before heat treatment (average particle size of heat-expandable microspheres) is not particularly limited, but is preferably 5 to 100 μm (tentative). When D0 is 1 μm or more, the expansion performance of the heat-expandable microspheres tends to be improved, and when it is 100 μm or less, the appearance of the obtained molded article tends to be better. The lower limit of D0 is more preferably 10 μm, even more preferably 15 μm, and the upper limit of D0 is more preferably 70 μm, even more preferably 60 μm, and particularly preferably 50 μm.
[0018] The heat-expandable microspheres of the present invention preferably satisfy the following condition 2. Condition 2: In thermogravimetry, the heat-expandable microspheres have a circularity of 0.8 or more after heat treatment when the blowing agent content is reduced by 95% by weight.
[0019] By further satisfying the above condition 2, the shape of the pores introduced into the molded body becomes uniform, even when the temperature during production of the molded body is high or the heating time is long, and molded bodies that are lightweight and have a good appearance tend to be obtained more stably. The circularity of the heat-expandable microspheres that have been heat-treated under the above condition 2 is more preferably at least 0.85, further preferably at least 0.90, and particularly preferably at least 0.95. The upper limit of the circularity is preferably 1.0. The sphericity of the heat-expandable microspheres after heat treatment when the blowing agent content is reduced by 95% by weight is measured by the method described in the Examples.
[0020] The expansion starting temperature (T s) is not particularly limited, but in terms of achieving the effects of the present invention, it is preferably 120°C or higher, more preferably 140°C or higher, and particularly preferably 150°C or higher. On the other hand, the upper limit of the expansion starting temperature is preferably 250°C, more preferably 200°C, still more preferably 180°C, and particularly preferably 160°C.
[0021] The maximum expansion temperature (T max ) is not particularly limited, but in terms of achieving the effects of the present invention, it is preferably 160°C or higher, more preferably 180°C or higher, and particularly preferably 200°C or higher. The upper limit of the maximum expansion temperature is preferably 300°C, more preferably 280°C, even more preferably 250°C, and particularly preferably 230°C. The expansion starting temperature (T s ) and maximum expansion temperature (T max ) is measured by the method described in the Examples.
[0022] The maximum volume expansion ratio of the heat-expandable microspheres of the present invention is not particularly limited, but is preferably 5 to 200 times (tentative). When the expansion ratio is 5 times or more, a lightweight molded article tends to be obtained. On the other hand, when the expansion ratio is 200 times or less, the appearance of the obtained molded article tends to be better. The lower limit of the expansion ratio is more preferably 10 times, and even more preferably 13 times. On the other hand, the upper limit of the expansion ratio is more preferably 180 times, and even more preferably 150 times.
[0023] In the heat-expandable microspheres of the present invention, it is preferable that the thermoplastic resin (A) forming the outer shell is a polymer of a polymerizable component containing a monomer having one polymerizable carbon-carbon double bond (hereinafter sometimes referred to as a non-crosslinkable monomer), because this allows the blowing agent to be efficiently encapsulated and the microspheres have high expansion performance. The polymerizable component may also contain a monomer having at least two polymerizable carbon-carbon double bonds (hereinafter, sometimes simply referred to as a crosslinkable monomer). Both the non-crosslinkable monomer and the crosslinkable monomer are components capable of undergoing an addition reaction, and the crosslinkable monomer is a component capable of introducing a crosslinked structure into the thermoplastic resin (A).
[0024] The polymerizable component may contain a carboxyl group-containing monomer as a non-crosslinkable monomer. The polymerizable component preferably contains a carboxyl group-containing monomer, since the heat resistance of the heat-expandable microspheres is improved. Furthermore, the inclusion of a carboxyl group-containing monomer is preferable, since the microspheres tend to maintain their spherical shape after expansion even if they are subjected to a large thermal history. Examples of the carboxyl group-containing monomer include unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, ethacrylic acid, crotonic acid, and cinnamic acid; unsaturated dicarboxylic acids such as maleic acid, itaconic acid, fumaric acid, citraconic acid, and chloromaleic acid; anhydrides of unsaturated dicarboxylic acids; and unsaturated dicarboxylic acid monoesters such as monomethyl maleate, monoethyl maleate, monobutyl maleate, monomethyl fumarate, monoethyl fumarate, monomethyl itaconate, monoethyl itaconate, and monobutyl itaconate. These carboxyl group-containing monomers may be used alone or in combination of two or more kinds. A part or all of the carboxyl groups of the carboxyl group-containing monomer may be neutralized during or after polymerization.
[0025] When the polymerizable component contains a carboxyl group-containing monomer, the weight ratio of the carboxyl group-containing monomer in the polymerizable component is not particularly limited, but is preferably 5 to 70% by weight. If the weight ratio is within the above range, the shape after thermal expansion tends to be more likely to maintain a spherical shape even if it is subjected to a large thermal history. The lower limit of the weight ratio is more preferably 10% by weight, and even more preferably 15% by weight. On the other hand, the upper limit of the weight ratio is more preferably 50% by weight, even more preferably 40% by weight, and particularly preferably 35% by weight.
[0026] When the polymerizable component contains a carboxyl group-containing monomer, the polymerizable component may further contain a monomer having a group reactive with a carboxyl group as a non-crosslinkable monomer. When the polymerizable component contains a monomer having a group reactive with a carboxyl group, the monomer reacts with the carboxyl group during the thermal expansion of the heat-expandable microspheres, improving the density of the thermoplastic resin and making it difficult for deformation to occur, and thus enabling stable production of lightweight molded products with excellent appearance even under conditions of high temperature or long heating time during production of the molded products, which is preferable.
[0027] Examples of the group that reacts with a carboxyl group include a methylol group, a hydroxyl group, an amino group, an epoxy group, and an isocyanate group. Examples of monomers having a group that reacts with a carboxyl group include N-methylol (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, vinyl glycidyl ether, propenyl glycidyl ether, glycidyl (meth)acrylate, glycerin mono(meth)acrylate, 4-hydroxybutyl acrylate glycidyl ether, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, and p-hydroxystyrene, and these monomers may be used alone or in combination. The term (meth)acryl means acrylic or methacrylic, and the term (meth)acrylate means acrylate or methacrylate.
[0028] The polymerizable component may contain a nitrile monomer as a non-crosslinkable monomer. When the polymerizable component contains a nitrile monomer, the gas barrier properties of the thermoplastic resin (A) are increased, and the expansion performance is further improved, which is preferable. Examples of the nitrile monomer include acrylonitrile, methacrylonitrile, fumaronitrile, maleonitrile, etc., and these nitrile monomers may be used alone or in combination of two or more kinds.
[0029] When the polymerizable component contains a nitrile monomer, the weight ratio of the nitrile monomer in the polymerizable component is not particularly limited, but is preferably 25 to 95% by weight. The lower limit of the weight ratio is more preferably 30% by weight, even more preferably 40% by weight, particularly preferably 45% by weight, and most preferably 50% by weight. On the other hand, the upper limit of the weight ratio is more preferably 90% by weight, even more preferably 85% by weight, and particularly preferably 80% by weight.
[0030] The nitrile monomer preferably contains at least one selected from acrylonitrile (AN) and methacrylonitrile (MAN) since this improves the solvent resistance of the heat-expandable microspheres. When the nitrile monomer contains acrylonitrile and methacrylonitrile, the weight ratio of acrylonitrile and methacrylonitrile (AN / MAN) is not particularly limited, but is preferably 10 / 90 to 90 / 10. When the weight ratio is within the above range, the expansion performance tends to be improved. The lower limit of the weight ratio is more preferably 25 / 75, even more preferably 40 / 60, and particularly preferably 50 / 50. On the other hand, the upper limit of the weight ratio is more preferably 85 / 15, and even more preferably 80 / 20.
[0031] When the polymerizable component contains a nitrile monomer and a carboxyl group-containing monomer, the total weight ratio of the nitrile monomer and the carboxyl group-containing monomer in the polymerizable component is not particularly limited, but is preferably 50 to 100% by weight. When the total amount is 50% by weight or more, the outer shell of the heat-expandable microspheres tends to have high gas barrier properties and sufficient heat resistance. The lower limit of the total amount is more preferably 60% by weight, and even more preferably 70% by weight. On the other hand, the upper limit of the total amount is more preferably 99% by weight, even more preferably 97% by weight, and particularly preferably 95% by weight.
[0032] The polymerizable component may contain other non-crosslinkable monomers in addition to the non-crosslinkable monomers described above. Examples of other non-crosslinkable monomers include vinyl halide monomers such as vinyl chloride; vinylidene halide monomers such as vinylidene chloride; vinyl ester monomers such as vinyl acetate, vinyl propionate, and vinyl butyrate; (meth)acrylic acid aliphatic ester monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, stearyl (meth)acrylate, phenyl (meth)acrylate, isobornyl (meth)acrylate, and cyclohexyl (meth)acrylate; and (meth)acrylic acid aliphatic ester monomers such as benzyl (meth)acrylate. Examples of suitable monomers include aromatic ester monomers; (meth)acrylamide monomers such as acrylamide, substituted acrylamide, methacrylamide, and substituted methacrylamide; maleimide monomers such as N-phenylmaleimide and N-cyclohexylmaleimide; styrene monomers such as styrene and α-methylstyrene; ethylenically unsaturated monoolefin monomers such as ethylene, propylene, and isobutylene; vinyl ether monomers such as vinyl methyl ether, vinyl ethyl ether, and vinyl isobutyl ether; vinyl ketone monomers such as vinyl methyl ketone; N-vinyl monomers such as N-vinylcarbazole and N-vinylpyrrolidone; and vinyl naphthalene salts.
[0033] As described above, the polymerizable component may contain a crosslinkable monomer, which improves the density of the outer shell of the heat-expandable microspheres and suppresses leakage of the blowing agent during thermal expansion, thereby enabling effective expansion. Examples of the crosslinkable monomer include alkanediol di(meth)acrylates such as ethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-methyl-1,5 pentanediol di(meth)acrylate, and 2-methyl-1,8 octanediol di(meth)acrylate; di(meth)acrylate, triethylene glycol di(meth)acrylate, PEG#200 di(meth)acrylate, PEG#400 di(meth)acrylate, PEG#600 di(meth)acrylate, PEG#1000 di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol #400 di(meth)acrylate, polypropylene glycol #700 di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, Polyalkylene glycol di(meth)acrylates such as polytetramethylene glycol #650 di(meth)acrylate and ethoxylated polypropylene glycol #700 di(meth)acrylate;Ethoxylated bisphenol A di(meth)acrylate (EO addition 2-30);Propoxylated bisphenol A di(meth)acrylate;Propoxylated ethoxylated bisphenol A di(meth)acrylate;Glycerin di(meth)acrylate;Polybutadiene di(meth)acrylate;Polyisoprene di(meth)acrylate;2-Hydroxy 3-Acryloyloxypropyl methacrylate;Dimethylol-tricyclodecane di(meth)acrylate;Divinylbenzene;Ethoxylated glycerin triacrylate;1,3,5-Tri(meth)acryloyl hexahydro-1,3,5-triazine;Triallyl isocyanurate;Pentaerythritol tri(meth)acrylate;Trimethylolpropane tri(meth)acrylate;1,2,4-Trivinylbenzene;Ditrimethylolpropane tetra(meth)acrylate;Pentaerythritol tetra(meth)acrylate;Examples of the crosslinkable monomer include a bifunctional crosslinkable monomer such as dipentaerythritol hexa(meth)acrylate, a trifunctional crosslinkable monomer, and a tetrafunctional or higher crosslinkable monomer. These crosslinkable monomers may be used alone or in combination of two or more.
[0034] The weight ratio of the crosslinkable monomer in the polymerizable component is not particularly limited, but is preferably 0.1 to 10% by weight. The lower limit of the weight ratio is more preferably 0.2% by weight, particularly preferably 0.3% by weight, and most preferably 0.4% by weight. On the other hand, the upper limit of the weight ratio is more preferably 7% by weight, even more preferably 5% by weight, particularly preferably 3% by weight, and most preferably 2% by weight.
[0035] The blowing agent (B) is a component that vaporizes when heated and is encapsulated in the outer shell of the heat-expandable microspheres, which gives the heat-expandable microspheres thermal expandability (the property that the entire microsphere expands when heated) throughout the microsphere. Examples of the blowing agent (B) include hydrocarbons having 1 to 13 carbon atoms, such as methane, ethane, propane, (iso)butane, (iso)pentane, (iso)hexane, (iso)heptane, (iso)octane, (iso)nonane, (iso)decane, (iso)undecane, (iso)dodecane, and (iso)tridecane; hydrocarbons having more than 13 and not more than 20 carbon atoms, such as (iso)hexadecane and (iso)eicosane; and petroleum fractions such as pseudocumene, petroleum ether, and normal paraffins and isoparaffins having an initial boiling point of 150 to 260° C. and / or a distillation range of 70 to 360° C. halides of hydrocarbons having 1 to 12 carbon atoms, such as methyl chloride, methylene chloride, chloroform, and carbon tetrachloride; fluorine-containing compounds, such as hydrofluoroethers; silanes having an alkyl group having 1 to 5 carbon atoms, such as tetramethylsilane, trimethylethylsilane, trimethylisopropylsilane, and trimethyl-n-propylsilane; and compounds that undergo thermal decomposition upon heating to generate a gas, such as azodicarbonamide, N,N'-dinitrosopentamethylenetetramine, and 4,4'-oxybis(benzenesulfonylhydrazide). The blowing agent (B) may be composed of one kind of compound or a mixture of two or more kinds of compounds. The blowing agent may be linear, branched, or alicyclic, and is preferably aliphatic. The blowing agent (B) preferably contains a hydrocarbon having 8 or more carbon atoms, which increases the maximum expansion temperature of the heat-expandable microspheres, and preferably contains a hydrocarbon having 5 or less carbon atoms, which allows the heat-expandable microspheres to expand more efficiently.
[0036] The content of the blowing agent (B) in the heat-expandable microspheres of the present invention is defined as the percentage of the weight of the blowing agent encapsulated in the heat-expandable microspheres to the total weight of the heat-expandable microspheres. The content of the foaming agent (B) is not particularly limited, but is preferably 2 to 40% by weight. When the encapsulation rate is within the above range, the foaming agent is less likely to leak out during thermal expansion, and the expandability tends to be improved. The lower limit of the content is more preferably 4% by weight, even more preferably 5% by weight, and particularly preferably 6% by weight. On the other hand, the upper limit of the content is more preferably 35% by weight, even more preferably 30% by weight, and particularly preferably 25% by weight.
[0037] The heat-expandable microspheres of the present invention may contain a component (C) having thermosetting properties. The heat-expandable microspheres containing component (C) are preferred because they harden when the heat-expandable microspheres are heated and expanded, reinforcing the shell and making the microspheres less susceptible to deformation. This allows for stable production of lightweight molded articles with excellent appearance even when the molded articles are produced at high temperatures or for long heating times.
[0038] Component (C) is not particularly limited, but it is preferable in terms of achieving the effects of the present invention if it has at least one functional group selected from a hydroxyl group, an alkoxy group, a methylol group, an epoxy group, and an amino group. When component (C) has the above-mentioned functional group, it is preferable that component (C) is a compound having two or more of the functional groups in one molecule, since this improves the strength after curing, further reinforces the outer shell of the expanded body of the heat-expandable microspheres, and suppresses deformation even when subjected to a large thermal history. When component (C) has two or more functional groups, the functional groups may be the same or different.
[0039] Examples of component (C) include thermosetting silicones such as silicone rubber, silicone resin, and silicone oligomer; epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, and glycidylamine type epoxy resin; phenol resins such as novolac type phenolic resin, resol type phenolic resin, and benzylic ether type phenolic resin; melamine resin, urea resin, polyimide resin, and bismaleimide resin, and these may be used alone or in combination of two or more.
[0040] When component (C) is contained, in terms of exerting the effects of the present invention, it is preferred that the component (C) be present in at least one of the following states: inside the outer shell of heat-expandable microspheres, on the inner surface of the outer shell, and encapsulated in the outer shell. The content of component (C) is not particularly limited, but is preferably 0.05 to 55 parts by weight relative to 100 parts by weight of the thermoplastic resin (A) constituting the shell. If the content is 0.05 parts by weight or more, the strength of component (C) after heat curing tends to be sufficient, and if the content is 55 parts by weight or less, the expansion performance tends to be improved. The lower limit of the content is 0.1 parts by weight, more preferably 0.3 parts by weight, particularly preferably 0.5 parts by weight, and most preferably 1 part by weight. On the other hand, the upper limit of the content is more preferably 50 parts by weight, even more preferably 40 parts by weight, particularly preferably 20 parts by weight, and most preferably 15 parts by weight.
[0041] The heat-expandable microspheres of the present invention are suitable for use in molding processes such as injection molding, extrusion molding, kneading molding, calendar molding, blow molding, compression molding, vacuum molding, thermoforming, etc., because they are suppressed from shrinking when expanded even when subjected to a very large thermal history, the shape of the pores introduced by the expansion of the heat-expandable microspheres is maintained, and lightweight molded articles with excellent appearance and suppressed surface depressions can be stably produced. They can also be used by mixing with paste-like materials such as PVC paste, or liquid compositions such as EVA emulsion, acrylic emulsion, and urethane binder.
[0042] [Method of producing heat-expandable microspheres] The heat-expandable microspheres of the present invention can be produced by a process comprising the steps of dispersing an oily mixture containing a polymerizable component, a blowing agent (B), a thermosetting component (C) if necessary, and a polymerization initiator in an aqueous dispersion medium and polymerizing the polymerizable component (hereinafter sometimes simply referred to as a polymerization step).
[0043] The polymerization initiator is not particularly limited, but examples thereof include peroxides and azo compounds. Examples of peroxides include peroxydicarbonates such as diisopropyl peroxydicarbonate, di-sec-butyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, and dibenzyl peroxydicarbonate; diacyl peroxides such as dilauroyl peroxide and dibenzoyl peroxide; ketone peroxides such as methyl ethyl ketone peroxide and cyclohexanone peroxide; peroxyketals such as 2,2-bis(t-butylperoxy)butane; hydroperoxides such as cumene hydroperoxide and t-butyl hydroperoxide; dialkyl peroxides such as dicumyl peroxide and di-t-butyl peroxide; and peroxy esters such as t-hexyl peroxypivalate and t-butyl peroxyisobutyrate. Examples of azo compounds include 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylpropionate), 2,2'-azobis(2-methylbutyronitrile), and 1,1'-azobis(cyclohexane-1-carbonitrile).
[0044] The amount of the polymerization initiator to be added is not particularly limited, but in terms of achieving the effects of the present application, it is preferably 0.05 to 10 parts by weight, more preferably 0.1 to 8 parts by weight, and even more preferably 0.2 to 5 parts by weight, relative to 100 parts by weight of the polymerizable component.
[0045] The aqueous dispersion medium used in the polymerization step is a medium mainly composed of water such as ion-exchanged water for dispersing the oily mixture, and may further contain an alcohol such as methanol, ethanol, propanol, etc., or a hydrophilic organic solvent such as acetone, etc. In the present invention, hydrophilicity means a state in which it can be arbitrarily mixed with water. The amount of the aqueous dispersion medium used is not particularly limited, but is preferably 100 to 1000 parts by weight based on 100 parts by weight of the polymerizable component.
[0046] The aqueous dispersion medium may further contain an electrolyte. It is preferable that the aqueous dispersion medium contains an electrolyte. When the aqueous dispersion medium contains an electrolyte and is in a dissolved state, the electrolyte has a salting-out effect to suppress dissolution of the polymerizable component in the aqueous dispersion medium, and a larger amount of the polymerizable component contributes to the reaction during the polymerization step, leading to an increase in the molecular chain of the polymer and an increase in the molecular weight of the polymer, which increases the degree of softening due to heat of the thermoplastic resin constituting the outer shell of the heat-expandable microspheres and the degree of viscosity during melting, making it easier to obtain the heat-expandable microspheres. Examples of the electrolyte include sodium chloride, magnesium chloride, calcium chloride, sodium sulfate, magnesium sulfate, ammonium sulfate, sodium carbonate, etc. These electrolytes may be used alone or in combination of two or more. The content of the electrolyte is not particularly limited, but is preferably 10 to 30 parts by weight, and more preferably 15 to 25 parts by weight, relative to 100 parts by weight of the aqueous dispersion medium.
[0047] The aqueous dispersion medium may contain at least one water-soluble compound selected from water-soluble 1,1-substituted compounds having a structure in which a hydrophilic functional group selected from a hydroxyl group, a carboxylic acid (salt) group, and a phosphonic acid (salt) group and a heteroatom are bonded to the same carbon atom, polyalkyleneimines having a structure in which an alkyl group substituted with a hydrophilic functional group selected from a carboxylic acid (salt) group and a phosphonic acid (salt) group is bonded to a nitrogen atom, water-soluble ascorbic acids, water-soluble polyphenols, water-soluble vitamin B, potassium dichromate, alkali metal nitrite, metal (III) halide, boric acid, and water-soluble phosphonic acids (salts). Note that water-soluble in the present invention means a state in which 1 g or more is dissolved in 100 g of water. The amount of the water-soluble compound contained in the aqueous dispersion medium is not particularly limited, but is preferably 0.0001 to 1.0 part by weight, more preferably 0.0003 to 0.1 part by weight, and even more preferably 0.001 to 0.05 part by weight, relative to 100 parts by weight of the polymerizable component.
[0048] The aqueous dispersion medium may contain a dispersion stabilizer or a dispersion stabilization assistant in addition to the electrolyte and the water-soluble compound. Examples of the dispersion stabilizer include tribasic calcium phosphate, magnesium pyrophosphate obtained by a double decomposition method, calcium pyrophosphate, colloidal silica, alumina sol, magnesium hydroxide, etc. These dispersion stabilizers may be used alone or in combination of two or more kinds. The amount of the dispersion stabilizer to be added is not particularly limited, but is preferably 0.05 to 100 parts by weight, and more preferably 0.2 to 70 parts by weight, based on 100 parts by weight of the polymerizable component. Examples of the dispersion stabilization assistant include surfactants such as polymer-type dispersion stabilization assistants, cationic surfactants, anionic surfactants, amphoteric surfactants, nonionic surfactants, etc. These dispersion stabilization assistants may be used alone or in combination of two or more kinds.
[0049] The aqueous dispersion medium is prepared, for example, by blending water (ion-exchanged water) with an electrolyte, a water-soluble compound, a dispersion stabilizer, a dispersion stabilization assistant, etc., as necessary. The pH of the aqueous dispersion medium during polymerization is appropriately determined depending on the types of the water-soluble compound, the dispersion stabilizer, and the dispersion stabilization assistant. In the (intermediate) polymerization step, polymerization may be carried out in the presence of sodium hydroxide, or sodium hydroxide and zinc chloride.
[0050] In the polymerization step, the oily mixture is suspended and dispersed in an aqueous dispersion medium so as to prepare spherical oil droplets having a predetermined particle size. Examples of methods for suspending and dispersing an oily mixture include general dispersion methods such as stirring with a homomixer (e.g., manufactured by Primix Corporation) or using a static dispersion device such as a static mixer (e.g., manufactured by Noritake Engineering Co., Ltd.), a membrane suspension method, and an ultrasonic dispersion method. The suspension polymerization is then initiated by heating the dispersion in which the oily mixture is dispersed in the aqueous dispersion medium as oil globules. During the polymerization reaction, the dispersion is preferably stirred, and the stirring may be carried out gently enough to prevent, for example, the floating of the monomers and the settling of the heat-expandable microspheres after polymerization.
[0051] The polymerization temperature is freely set depending on the type of polymerization initiator, but is preferably controlled to 30 to 90° C., more preferably 40 to 88° C. The reaction temperature is preferably maintained for about 1 to 20 hours. The initial polymerization pressure is not particularly limited, but is 0 to 5 MPa, more preferably 0.2 to 3 MPa, in terms of gauge pressure.
[0052] The slurry obtained after the polymerization step is filtered using a centrifuge, a pressure press, a vacuum dehydrator, or the like to obtain a cake-like product having a moisture content of 10 to 50% by weight, preferably 15 to 45% by weight, and more preferably 20 to 40% by weight. The cake-like product is then dried using a tray dryer, an indirect heating dryer, a fluidized bed dryer, a vacuum dryer, a vibration dryer, an airflow dryer, or the like to obtain a dry powder having a moisture content of 5% by weight or less, preferably 3% by weight or less, and more preferably 1% by weight or less. In order to reduce the content of ionic substances such as electrolytes, the cake-like product may be washed with water or redispersed, filtered, and dried. The slurry may be dried using a spray dryer, fluidized bed dryer, or the like to obtain a dry powder.
[0053] [Hollow particles] The hollow particles of the present invention are particles obtained by heating and expanding the above-described heat-expandable microspheres. The hollow particles are lightweight and have excellent material properties when incorporated into compositions or molded products.
[0054] The hollow particles of the present invention are not particularly limited, but can be obtained by heating and expanding the above-mentioned heat-expandable microspheres preferably at 100 to 450°C. The method for producing the hollow particles is not particularly limited, and may be either a dry thermal expansion method or a wet thermal expansion method. The dry thermal expansion method includes the method described in JP-A-2006-213930, particularly the internal injection method. Another dry thermal expansion method includes the method described in JP-A-2006-96963. The wet thermal expansion method includes the method described in JP-A-62-201231.
[0055] The volume average particle diameter of the hollow particles of the present invention (hereinafter sometimes simply referred to as the average particle diameter) is not particularly limited because it can be freely designed according to the application, but is preferably 6 to 300 μm in terms of suppressing deformation of the hollow particles. The lower limit of the average particle diameter is more preferably 10 μm, even more preferably 15 μm, and particularly preferably 20 μm. On the other hand, the upper limit of the average particle diameter is more preferably 250 μm, and even more preferably 200 μm. The coefficient of variation CV of the particle size distribution of the hollow particles of the present invention is not particularly limited, but is preferably 35% or less, more preferably 30% or less, and particularly preferably 25% or less.
[0056] The true specific gravity of the hollow particles of the present invention is not particularly limited, but is preferably 0.005 to 0.6. If the true specific gravity is 0.005 or more, the hollow particles tend to be prevented from deforming, and if the true specific gravity is 0.6 or less, the hollow particles tend to function more efficiently as a weight-reducing agent. The lower limit of the true specific gravity is more preferably 0.01, even more preferably 0.015, and particularly preferably 0.020. On the other hand, the upper limit of the true specific gravity is more preferably 0.4, and even more preferably 0.3.
[0057] [Hollow particles with fine particles attached] The microparticle-coated hollow particles of the present invention include the hollow particles described above and microparticles that are attached to the outer surface of the shell of the hollow particle. As shown in Fig. 2, the microparticle-coated hollow particles may be composed of microparticles (4 or 5) that are attached to the outer surface of the shell 2. The term "attached" here means that the microparticles may simply be adsorbed onto the outer surface of the shell 2 of the hollow particle (the state of microparticle 4 in Fig. 2), or that the thermoplastic resin that forms the shell near the outer surface is melted by heating, and the microparticles are embedded in and fixed to the outer surface of the shell of the hollow particle (the state of microparticle 5 in Fig. 2). By adhering the fine particles to the hollow particles, scattering of the hollow particles can be suppressed, and handling can be improved, and dispersibility in base components such as binders and resins can also be improved.
[0058] Various types of fine particles can be used, and may be made of either inorganic or organic materials. The shape of the fine particles may be amorphous or spherical, and examples of the shape of the fine particles include spherical, needle-like, and plate-like. Examples of inorganic substances constituting the fine particles include wollastonite, sericite, kaolin, mica, clay, talc, bentonite, alumina silicate, pyrophyllite, montmorillonite, calcium silicate, calcium carbonate, magnesium carbonate, dolomite, calcium sulfate, barium sulfate, glass flakes, boron nitride, silicon carbide, silica, alumina, mica, titanium dioxide, zinc oxide, magnesium oxide, zinc oxide, hydrosaltite, carbon black, molybdenum disulfide, tungsten disulfide, ceramic beads, glass beads, quartz beads, and glass microballoons.
[0059] Examples of organic substances constituting the fine particles include sodium carboxymethylcellulose, hydroxyethylcellulose, methylcellulose, ethylcellulose, nitrocellulose, hydroxypropylcellulose, sodium alginate, polyvinyl alcohol, polyvinylpyrrolidone, sodium polyacrylate, carboxyvinyl polymer, polyvinyl methyl ether, magnesium stearate, calcium stearate, zinc stearate, polyethylene wax, lauric acid amide, myristic acid amide, palmitic acid amide, stearic acid amide, hydrogenated castor oil, (meth)acrylic resin, polyamide resin, urethane resin, polyethylene resin, polypropylene resin, and fluorine-based resin. The inorganic or organic matter constituting the fine particles may be treated with a surface treatment agent such as a silane coupling agent, paraffin wax, fatty acid, resin acid, urethane compound, or fatty acid ester, or may be untreated.
[0060] The average particle size of the fine particles is not particularly limited, but is preferably 0.001 to 30 μm, more preferably 0.005 to 25 μm, and particularly preferably 0.01 to 20 μm. The average particle size of the fine particles referred to here is the particle size of the fine particles measured by a laser diffraction method. The ratio of the average particle diameter of the fine particles to the average particle diameter of the hollow particles (average particle diameter of the fine particles / volume average particle diameter of the hollow particles) is preferably 1 or less, more preferably 0.1 or less, and even more preferably 0.05 or less, from the viewpoint of adhesion of the fine particles to the surfaces of the hollow particles.
[0061] The weight ratio of the fine particles to the whole fine particle-coated hollow particles is not particularly limited, but is preferably 20 to 95% by weight. The lower limit of the weight ratio is more preferably 40% by weight. On the other hand, the upper limit of the weight ratio is more preferably 90% by weight or less, even more preferably 85% by weight or less, and particularly preferably 80% by weight or less.
[0062] The true specific gravity of the microparticle-coated hollow particles of the present invention is not particularly limited, but is preferably 0.05 to 0.6. If the true specific gravity is 0.03 or more, the hollow particles tend to be prevented from deforming, and if the true specific gravity is 0.6 or less, the particles tend to function more efficiently as a weight-reducing agent. The lower limit of the true specific gravity is more preferably 0.1, and even more preferably 0.12. On the other hand, the upper limit of the true specific gravity is more preferably 0.3, and even more preferably 0.2.
[0063] When the fine particle-coated hollow particles of the present invention are blended with a composition described below, they are useful as a coating composition or an adhesive composition. The method for producing the fine particle-coated hollow particles of the present invention is not particularly limited, but preferably includes the following mixing step and adhesion step. Mixing step: A step of mixing the heat-expandable microspheres and fine particles. Adhesion step: a step of heating the mixture obtained in the mixing step to a temperature above the softening point of the thermoplastic resin forming the outer shell of the heat-expandable microspheres to expand the heat-expandable microspheres and to adhere fine particles to the outer surface of the resulting hollow particles.
[0064] [Composition and Molded Article] The composition of the present invention contains at least one material selected from the group consisting of the above-described heat-expandable microspheres, hollow particles, and microparticle-coated hollow particles (hereinafter sometimes simply referred to as particulate material), and a base component. Examples of base material components include rubbers such as natural rubber, butyl rubber, silicone rubber, and ethylene-propylene-diene rubber (EPDM); thermosetting resins such as unsaturated polyester, epoxy resin, and phenolic resin; waxes such as polyethylene wax and paraffin wax; ethylene-vinyl acetate copolymer (EVA), ionomer, polyethylene, polypropylene, polyvinyl chloride (PVC), acrylic resin, thermoplastic polyurethane, acrylonitrile-styrene copolymer (AS resin), acrylonitrile-butadiene-styrene copolymer (ABS resin), polystyrene (PS), polyamide resin (nylon 6, nylon 66, etc.), polycarbonate, polyethylene, Examples of the base material include thermoplastic resins such as polypropylene terephthalate (PET), polybutylene terephthalate (PBT), polyacetal (POM), and polyphenylene sulfide (PPS); thermoplastic elastomers such as olefin-based elastomers and styrene-based elastomers; bioplastics such as polylactic acid (PLA), cellulose acetate, PBS, PHA, and starch resins; sealing materials such as silicone-based, modified silicone-based, polysulfide-based, modified polysulfide-based, urethane-based, acrylic-based, polyisobutylene-based, and butyl rubber-based materials; urethane-based, ethylene-vinyl acetate copolymer-based, vinyl chloride-based, and acrylic-based paint components; and inorganic materials such as cement, mortar, and cordierite. These base material components may be used alone or in combination of two or more types.
[0065] The composition of the present invention may contain other ingredients as necessary. Examples of other components include reinforcing fibers such as glass fiber, carbon fiber, and natural fiber; inorganic powders such as talc, titanium oxide, silica, calcium carbonate, and inorganic pigments; polymeric fine particles such as acrylic fine particles, styrene fine particles, urethane fine particles, and silicone fine particles; pigments; flame retardants; chemical foaming agents; and oils such as silicone oil and paraffin oil.
[0066] The amount of the particulate material contained in the composition of the present invention is preferably 0.1 to 20 parts by weight based on 100 parts by weight of the base component. When the content is within the above range, a composition that is lightweight and maintains the physical properties of the base component can be obtained. The upper limit of the content is more preferably 15 parts by weight, even more preferably 13 parts by weight, and particularly preferably 10 parts by weight. On the other hand, the lower limit of the content is more preferably 0.3 parts by weight, even more preferably 0.5 parts by weight, and particularly preferably 1 part by weight.
[0067] The method for producing the composition of the present invention is not particularly limited, but is preferably a method in which the components are mixed using a kneader, roll, mixing roll, mixer, single-screw kneader, twin-screw kneader, multi-screw kneader, or the like. The applications of the composition of the present invention include, for example, molding compositions, coating compositions, clay compositions, fiber compositions, adhesive compositions, powder compositions, and the like.
[0068] The composition of the present invention may be a molding masterbatch. In particular, when the molding masterbatch contains heat-expandable microspheres, it is preferable to use a base component that softens or melts at a temperature lower than the expansion initiation temperature of the heat-expandable microspheres. Examples of the base material component that softens or melts at a temperature lower than the expansion initiation temperature of the heat-expandable microspheres include waxes such as polyethylene wax and paraffin wax; thermoplastic resins such as ethylene-vinyl acetate copolymer (EVA), polyethylene, modified polyethylene, polypropylene, modified polypropylene, modified polyolefin, polyvinyl chloride (PVC), acrylic resin, thermoplastic polyurethane, acrylonitrile-styrene copolymer (AS resin), acrylonitrile-butadiene-styrene copolymer (ABS resin), polystyrene (PS), polycarbonate, polyethylene terephthalate (PET), and polybutylene terephthalate (PBT); ionomer resins such as ethylene-based ionomer, urethane-based ionomer, styrene-based ionomer, and fluorine-based ionomer; and thermoplastic elastomers such as olefin-based elastomer, styrene-based elastomer, and urethane-based elastomer. The molding masterbatch can be used when producing a resin molded article by a method such as extrusion molding, injection molding, or press molding, and is preferably used as a method for introducing air bubbles into a resin molded article.
[0069] When a resin molded body is manufactured using a molding masterbatch, the resin used may be selected from the above-mentioned base components, and examples of the resin include ethylene-vinyl acetate copolymer (EVA), polyethylene, modified polyethylene, polypropylene, modified polypropylene, modified polyolefin, polyvinyl chloride (PVC), acrylic resin, thermoplastic polyurethane, acrylonitrile-styrene copolymer (AS resin), acrylonitrile-butadiene-styrene copolymer (ABS resin), polystyrene (PS), nylon 6, nylon 66, modified polyamide, polycarbonate, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and the like. ), polyacetal (POM), polyphenylene sulfide (PPS), polyphenylene ether (PPE), modified polyphenylene ether, ionomer resin, olefin-based elastomer, styrene-based elastomer, polyester-based elastomer, polylactic acid (PLA), cellulose acetate, PBS, PHA, starch resin, natural rubber, isoprene rubber (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), chloroprene rubber (CR), nitrile rubber (NBR), butyl rubber, silicone rubber, acrylic rubber, urethane rubber, fluororubber, ethylene-propylene-diene rubber (EPDM), and mixtures thereof.
[0070] When the composition of the present invention is a molding masterbatch, the amount of granular material contained in the molding masterbatch is not particularly limited, but is more than 20 parts by weight and not more than 750 parts by weight per 100 parts by weight of the base component. When the content is within the above range, the dispersibility of the granular material is good, and a lightweight molded product tends to be obtained. The upper limit of the content is more preferably 500 parts by weight, even more preferably 300 parts by weight, and particularly preferably 200 parts by weight. On the other hand, the lower limit of the content is more preferably 40 parts by weight, and even more preferably 50 parts by weight.
[0071] The molded article of the present invention is obtained by molding the composition described above. Examples of the molded article of the present invention include coating films and molded articles. The molded article of the present invention has improved physical properties such as light weight, porosity, sound absorption, heat insulation, low thermal conductivity, low dielectric constant, design, impact absorption, strength, chipping resistance, etc. In addition to these, other expected effects include stabilization against sink marks and warping, reduction in molding shrinkage, dimensional stability, etc. Moreover, a molded body containing an inorganic substance as a base component can be further fired to obtain a ceramic filter or the like. EXAMPLES
[0072] The heat-expandable microspheres of the present invention will now be described in detail with reference to examples. However, the present invention is not limited to these examples. In the following examples and comparative examples, "%" means "% by weight" and "parts" means "parts by weight" unless otherwise specified. Furthermore, in the following, heat-expandable microspheres may be referred to as "microspheres" for simplicity.
[0073] [Expansion start temperature of thermally expandable microspheres (T s ) and maximum expansion temperature (T max )〕 A DMA (DMA Q800, manufactured by TA Instruments) was used as the measuring device. 0.5 mg of microspheres was placed in an aluminum cup with a diameter of 6.0 mm and a depth of 4.8 mm, and an aluminum lid (diameter 5.6 mm, thickness 0.1 mm) was placed on top of the microsphere layer to prepare a sample. The sample height was measured while a force of 0.01 N was applied from above using a pressure rod. With a force of 0.01 N applied using the pressure rod, the sample was heated from 20°C to 350°C at a heating rate of 10°C / min, and the displacement of the pressure rod in the vertical direction was measured. The temperature at which displacement in the forward direction began was defined as the expansion beginning temperature (T s ) and the temperature at which the maximum displacement occurred was the maximum expansion temperature (T max ) was decided.
[0074] [Water content of thermally expandable microspheres] The measurement was performed using a Karl Fischer moisture meter (Model MKA-510N, manufactured by Kyoto Electronics Manufacturing Co., Ltd.). The moisture content (wt%) of the heat-expandable microspheres was measured using w1 It was decided.
[0075] [Measurement of blowing agent content (C1) of heat-expandable microspheres] 1.0 g of the heat-expandable microspheres were placed in a stainless steel evaporating dish with a diameter of 80 mm and a depth of 15 mm, and its weight (W1(g)) was measured. 30 ml of acetonitrile was added to disperse the microspheres uniformly, and the microspheres were left at room temperature for 24 hours, and then dried under reduced pressure at 130°C for 2 hours, after which their weight (W2(g)) was measured. The content of the blowing agent in the heat-expandable microspheres (C1, weight %) was calculated according to the following formula: w1 was measured by the method described above. C1 = 100 × {100 × (W1-W2) / 1.0-C w1} / (100-C w1 )
[0076] [Thermogravimetric measurement of heat-expandable microspheres] The thermogravimetric measurement was performed using a thermogravimetric analyzer (TGA Q500, manufactured by TA Instruments) according to the following steps A and B. (Step A: Measurement when the blowing agent content of heat-expandable microspheres is reduced by 95% by weight) The heat-expandable microspheres W (g) were placed in a 500 μL alumina pan and heated from 25°C to 50°C at a heating rate of 10°C / min. To remove the moisture contained in the heat-expandable microspheres, the microspheres were kept at 50°C for 30 minutes, and it was confirmed that the weight change was constant. Next, thermogravimetry was performed at a heating rate of 10°C / min from 50°C to 500°C. The temperature (T Rg95 ) was decided. (Process B:T Rg95 Heat-treated heat-expandable microspheres in A sample of heat-expandable microspheres was prepared in the same manner as in step A above. The prepared sample was heated from 25°C to 50°C at a heating rate of 10°C / min, held at 50°C for 30 min, and then heated from 50°C to the T determined in step A. Rg95 The temperature was increased at a rate of 10°C / min up to 10°C. T Rg95 After the temperature reached 100° C., the sample was cooled to 30° C. or lower and taken out. The resultant product was used as heat-treated heat-expandable microspheres.
[0077] [Average particle size D0 of heat-expandable microspheres before heat treatment] The measurements were performed by image analysis based on images of the surfaces of the heat-expandable microspheres before the heat treatment, taken using a scanning electron microscope. Specifically, measurements and analysis were performed using image analysis-based particle size distribution measurement software Mac-View (Mountec Co., Ltd.). The pixel scale of the image to be analyzed was set in advance. Next, about 100 particles were randomly selected, the outer frame of the object was designated, and the area was calculated from the pixel count of the object to calculate the circle-equivalent diameter. The average of the calculated values was used as the average particle diameter D0 of the heat-expandable microspheres of the heat-treated product.
[0078] [Average particle size D1 of heat-treated heat-expandable microspheres] The average particle diameter D1 of the heat-expandable microspheres before heat treatment was measured in the same manner as described above, except that the measurement sample was the heat-treated heat-expandable microspheres obtained in step B.
[0079] [Circularity of heat-expandable microspheres after heat treatment] The measurements were performed by image analysis based on images of the surface of the heat-treated heat-expandable microspheres observed with a scanning electron microscope. The scale of the pixel number of the image to be subjected to image analysis was set in advance. Next, about 100 particles were randomly selected, the outer frame range of the object was specified, the area of the object surrounded by the frame and its perimeter were calculated, and the circularity of each sample was calculated using the following formula. The circularity of the heat-treated heat-expandable microspheres was calculated as the average of the calculated values. The closer the circularity is to 1, the closer it is to a perfect circle. Circularity = 4π × area ÷ (perimeter) 2
[0080] <Example 1> An aqueous dispersion medium was prepared by adding 110 parts of sodium chloride, 65 parts of colloidal silica containing 20% active ingredient, 0.9 parts of polyvinylpyrrolidone, and 0.04 parts of carboxymethylated polyethyleneimine sodium salt to 550 parts of ion-exchanged water and adjusting the pH to 3.0. Separately from this, 184 parts of acrylonitrile, 30 parts of methacrylonitrile, 24 parts of methacrylic acid, 3 parts of ethylene glycol dimethacrylate, 3 parts of di(2-ethylhexyl)peroxydicarbonate (P-OPP), 40 parts of isopentane, and 40 parts of silicone resin (manufactured by Shin-Etsu Chemical Co., Ltd., product name: KR-220L, containing two or more silanol groups) were mixed and dissolved to prepare an oily mixture. The aqueous dispersion medium and the oil mixture were mixed, and the resulting mixture was dispersed at 10,000 rpm for 1 minute using a homomixer (TK homomixer, manufactured by Plamix Co., Ltd.) to prepare a suspension. The suspension was transferred to a 1.5-liter pressurized reaction vessel and purged with nitrogen, and then polymerization reaction was carried out at a polymerization temperature of 60°C for 20 hours while stirring at 80 rpm under an initial reaction pressure of 0.35 MPa. After polymerization, the product was filtered and dried to obtain heat-expandable microspheres 1. The physical properties of the resulting heat-expandable microspheres are shown in Table 1.
[0081] <Examples 2 to 3, Comparative Examples 1 to 4> Heat-expandable microspheres were obtained in the same manner as in Example 1, except that the reaction conditions were changed as shown in Table 1. The physical properties of the obtained heat-expandable microspheres are shown in Table 1.
[0082] [Table 1]
[0083] Example A 50 parts of ethylene-vinyl acetate copolymer (melting point 66°C) as a base resin and 50 parts of the microspheres 1 obtained in Example 1 were added and kneaded in a pressure kneader at 75°C for 1 minute, and the kneaded mixture was extruded and shaped into pellets to obtain a master batch. 3 parts by weight of the obtained masterbatch was mixed with 97 parts by weight of high-density polyethylene resin (Novatec HD HY331, specific gravity 0.95, manufactured by Japan Polypropylene Corporation), and the obtained mixed composition was extruded in an extruder equipped with a T-die with the cylinder temperature and T-die temperature (molding temperature) set to 210°C to produce a foamed extruded sheet of 2 mm (thickness) x 150 mm (width). The molding temperature was changed to 190° C., 200° C., and 210° C. to obtain extrusion molded sheets in the same manner as in the case of the molding temperature of 210° C. The physical properties and evaluation of each of the obtained extrusion molded sheets were carried out by the methods described below. The results are shown in Table 2.
[0084] [Specific Gravity of Extrusion Molded Product] The specific gravity of the molded body was measured by the liquid immersion method using a precision specific gravity meter AX200 (manufactured by Shimadzu Corporation).
[0085] [State of bubbles in extrusion molded body] The bubble state of the cross section of the obtained molded product was confirmed using a scanning electron microscope (SEM). The ratio of closed bubbles per unit area was calculated from SEM photographs taken at 30x magnification, and judged based on the following evaluation criteria. ◎: Uniformly closed (closed bubble rate 80% or more) ○: Almost uniformly closed (closed cell rate is 50% or more but less than 80%) ×: Non-uniform (closed cell ratio less than 50%)
[0086] [Surface condition of extrusion molded body] An area of 15 cm length and 15 cm width on the surface of the obtained molded article was visually inspected and rated based on the following evaluation criteria. ○: Good (less than 3 uneven spots, no surface roughness) △: Slightly poor (surface roughness is slightly observed in 3 to 7 uneven areas) ×: Poor (more than 10 uneven spots and rough surface)
[0087] <Comparative Examples I~II> Except for changing to microspheres I or microspheres II, a batch was produced in the same manner as in Example A, and an extruded foam sheet was obtained using the batch in the same manner as in Example A. The properties and evaluation of each of the extruded foam sheets obtained were carried out in the same manner as in Example A. The results are shown in Table 2.
[0088] [Table 2]
[0089] Example B 50 parts of polyethylene resin (melting point 105°C) as a base resin and 50 parts of the microspheres 1 obtained in Example 2 were added and kneaded in a pressure kneader at 120°C for 1 minute, and the kneaded mixture was extruded and shaped into pellets to obtain a master batch. 3 parts by weight of the obtained masterbatch was mixed with 97 parts by weight of a styrene-based elastomer (Tuftec H1062, specific gravity 0.89, manufactured by Asahi Kasei Corporation), and the obtained mixed composition was extruded in an extruder equipped with a T-die with the cylinder temperature and T-die temperature (molding temperature) set to 220°C to produce a foamed extruded sheet having a thickness of 2 mm and a width of 150 mm. In addition, the molding temperature was changed to 230° C., 240° C., and 250° C. to obtain extrusion-molded sheets in the same manner as in the case of a molding temperature of 220° C. The physical properties and evaluation of each of the obtained extrusion-molded sheets were carried out in the same manner as in Example A. The results are shown in Table 3.
[0090] (Comparative Example III) Except for changing to microspheres III, a batch was produced in the same manner as in Example B, and an extrusion molded sheet was obtained using the batch in the same manner as in Example B. The properties and evaluation of each of the obtained extrusion foamed sheets were carried out in the same manner as in Example A. The results are shown in Table 3.
[0091] [Table 3]
[0092] Example C 50 parts of polyethylene resin (melting point 105°C) as a base resin and 50 parts of the microspheres 1 obtained in Example 3 were added and kneaded in a pressure kneader at 120°C for 1 minute, and the kneaded mixture was extruded and shaped into pellets to obtain a master batch. 7 parts by weight of the obtained master batch and 100 parts by weight of polycarbonate resin (Toughlon A2200, specific gravity 1.2, manufactured by Idemitsu Kosan Co., Ltd.) were mixed, and the obtained mixed composition was supplied to the hopper of an injection molding machine (manufactured by Japan Steel Works, Ltd., J85AD-110H, mold clamping force 85 tons), melt-kneaded, and injection molded to obtain a plate-shaped injection molded body having a width of 15 cm, a height of 12 cm, and a thickness of 7 mm. The molding conditions were set as follows: molding temperature 250°C, injection speed: 70 mm / sec, and mold temperature: 80°C, and injection molding was performed. Moreover, the injection temperature was changed to 260° C., 270° C., and 280° C. to obtain molded bodies in the same manner as in the case of a molding temperature of 250° C. The physical properties and evaluation of the obtained molded bodies were carried out by the methods described below. The results are shown in Table 4.
[0093] (Comparative example IV) Except for changing to microspheres III, a batch was produced in the same manner as in Example C, and an injection molded article was obtained using the batch in the same manner as in Example C. The physical properties and evaluation of the obtained injection molded article were performed in the same manner as in Example C. The results are shown in Table 4.
[0094] [Specific Gravity of Injection Molded Product] The specific gravity of the injection molded body was measured by the liquid immersion method using a precision specific gravity meter AX200 (manufactured by Shimadzu Corporation).
[0095] [State of bubbles in injection molded body] The bubble state of the cross section of the obtained injection molded product was confirmed using a scanning electron microscope (SEM). The ratio of closed bubbles per unit area was calculated from SEM photographs taken at 30x magnification, and judged based on the following evaluation criteria. ◎: Uniformly closed (closed bubble rate 80% or more) ○: Almost uniformly closed (closed cell rate is 50% or more but less than 80%) ×: Non-uniform (closed cell ratio less than 50%)
[0096] [Surface condition of injection molded body] The surface of the obtained injection molded article was visually inspected and rated based on the following evaluation criteria. ○: Good (less than 3 uneven spots on the surface) △: Slightly poor (surface irregularities are slightly observed in 3 to 7 places) ×: Poor (more than 10 uneven spots, surface unevenness is observed)
[0097] [Table 4]
[0098] It was confirmed from Examples A to C that the use of heat-expandable microspheres in which the ratio (D1 / D0) of the average particle size D1 of the heat-treated product when the blowing agent content was reduced by 95% by weight to the volume-average particle size D0 of the heat-expandable microspheres before the heat treatment was 1.2 or more enabled the stable production of lightweight molded articles with excellent appearance. On the other hand, if D1 / D0 is less than 1.2, it has been confirmed that a lightweight molded body with excellent appearance cannot be obtained when the temperature during production of the molded body is high or the heating time is long. [Explanation of symbols]
[0099] 1 Hollow particles with fine particles attached 2 Outer shell (outer shell) 3 Hollow part 4. Microparticles (adsorbed state) 5. Microparticles (embedded, fixed) 6. Shell containing thermoplastic resin 7. Core containing foaming agent
Claims
1. Heat-expandable microspheres comprising an outer shell containing a thermoplastic resin (A) and a blowing agent (B) encapsulated in the outer shell and vaporized by heating, Heat-expandable microspheres satisfying the following condition 1: Condition 1: In thermogravimetry, the ratio (D1 / D0) of the average particle size D1 of the heat-treated heat-expandable microspheres when the blowing agent content is reduced by 95% by weight to the average particle size D0 of the heat-expandable microspheres before the heat treatment is 1.2 or more.
2. 2. The heat-expandable microspheres according to claim 1, wherein the thermoplastic resin (A) is a polymer of a polymerizable component containing a carboxyl group-containing monomer.
3. The heat-expandable microspheres according to claim 1 or 2, further comprising a component (C) having thermosetting properties.
4. The heat-expandable microspheres according to claim 1 or 2, which satisfy the following condition 2: Condition 2: In thermogravimetry, the heat-expandable microspheres have a circularity of 0.8 or more when the blowing agent content is reduced by 95% by weight.
5. 2. Hollow particles which are expanded bodies of the heat-expandable microspheres according to claim 1.
6. 6. A microparticle-coated hollow particle comprising the hollow particle according to claim 5 and microparticles coated on an outer surface of an outer shell of the hollow particle.
7. A composition comprising at least one member selected from the group consisting of the heat-expandable microspheres according to claim 1 or 2, the hollow particles according to claim 5, and the microparticle-coated hollow particles according to claim 6, and a base component.
8. A molded article obtained by molding the composition according to claim 7.
Citation Information
Patent Citations
JP1967026524B1
Thermally expandable microsphere
JP2011256224A